Associations between socio demographic exposures, growth and development during infancy with development at the age of eight years among children: - Kakwangire, Paul; Ngari, Moses; Muhoozi, K. M. Grace; Westerberg, Cecilie Ane; Atukunda, Prudence; Iversen, O. Per (Journal of Global Health, 2024)
Background: Links between early life exposures and child development later in life are not sufficiently explored in low- and middle-income countries. We studied associations between sociodemographic variables, growth and development at six to eight months with developmental outcomes at eight years. Methods: We used data from a maternal education trial which included 511 mother-infant pairs at children’s age of six to eight months (baseline). In this follow-up study, data from 361 mother-child pairs were available. Questionnaires were used to collect sociodemographic variables. Growth (anthropometry) was measured by study personnel and converted to z-scores according to the World Health Organization (WHO) growth reference. Child development (cognitive, motor and language) at baseline was assessed using Bayley Scales of Infant and Todler Development, third edition (BSID-III). Development at eight years was measured using two neuropsychological tools: Kaufman Assessment Battery for Children Second Edition (KABC-II) and Test of Variables of Attention (TOVA). Results Higher weight-for-age z-scores (adjusted odds ratio (aOR) =0.74; 95% confidence interval (CI) =0.53, 0.98; P=0.04), better maternal education (aOR=0.86; 95% CI=0.78, 0.96; P=0.03). and better household head education (aOR=0.86; 95% CI=0.78, 0.96; P=0.03) at six to eight months of age were associated with lower odds of scoring below average on KABC-II categorical scores at eight years of age. Motor composite scores and maternal parity at six to eight months of age were positively associated with auditory and visual TOVA scores (all P-values <0.05) at eight years. Cognitive composite scores at six to eight months of age were positively associated with visual TOVA scores (P<0.05). In contrast, weight-for-length z-scores and household head age were negatively associated with both auditory and visual TOVA scores (P<0.05). Being a female child was associated with lower auditory and visual TOVA scores (P<0.05). Conclusions: At six to eight months of age, growth and development, gender, maternal education and parity, and household head age and education were associated with child development at eight years. Interventions emphasising improved growth and development in infancy, as well as parental educational attainment, may improve long-term developmental outcomes.
Analysis of a maternal education trial in rural Uganda
Article